2019
DOI: 10.15244/pjoes/99904
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Diversity and Biotechnological Potential of the Soil Ecosystem of a High-Mountainous Landfill

Abstract: Kumtor, the largest gold mine in Central Asia, is located southeast of the Kyrgyz Republic at an altitude of 4000 m a.s.l. in a partially glaciated permafrost zone at 41º52'N and 78º11'E. Its climate is continental, with an average annual temperature of-8ºC [1]. The Kumtor complex is in close proximity to the active glaciers [2] belonging to the Naryn River basin, which has international importance [3]. As a result of the largescale activity of the Kumtor gold mine, only 162.9 tons of oiled rags were formed at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
(40 reference statements)
0
7
0
Order By: Relevance
“…Totubaeva et al (2023) repaired the oil spill soil contamination site in extremely highmountainous conditions of Kyrgyz Republic through biostimulation (BS) and bioaugmentation (BA). 115 The results showed that the total number of bacteria increased by both two methods, and the BS treatment showed the highest total petroleum hydrocarbons biodegradation percentage 62.78% while the degradation ability of BS + BA decreased, and the total number of bacteria decreased, indicating the appropriate method depends on the specic environmental condition. Petroleum hydrocarbon as sole carbon source was degraded by a novel cold-adapted bacteria (Arthrobacter sp.…”
Section: Case Study On Restoration Using Cold-adapted Microbial Agentsmentioning
confidence: 92%
“…Totubaeva et al (2023) repaired the oil spill soil contamination site in extremely highmountainous conditions of Kyrgyz Republic through biostimulation (BS) and bioaugmentation (BA). 115 The results showed that the total number of bacteria increased by both two methods, and the BS treatment showed the highest total petroleum hydrocarbons biodegradation percentage 62.78% while the degradation ability of BS + BA decreased, and the total number of bacteria decreased, indicating the appropriate method depends on the specic environmental condition. Petroleum hydrocarbon as sole carbon source was degraded by a novel cold-adapted bacteria (Arthrobacter sp.…”
Section: Case Study On Restoration Using Cold-adapted Microbial Agentsmentioning
confidence: 92%
“…Bacteria were grown for 7 days on the shaker. The bacteria that were able to grow on oil contained medium were monitored spectrophotometrically at 590 nm (Specord 50, Analytik Jena GmbH) (Totubaeva et al 2019).…”
Section: Site Descriptionmentioning
confidence: 99%
“…These nutrients were added to contaminated soils and properly homogenised mechanically. Consortium of previously isolated indigenous microorganisms; Pseudomonas fluorescens P1, Rhodococcus rhodococcus R3 and Flavobacterium K1 (Brown et al 2017) was kept in nutrient broth (Totubaeva et al 2019). Consortium of these microorganisms was inoculated on the surface of bioaugmentation, biostimulation + bioaugmentation treatments and mixed mechanically.…”
Section: Site Descriptionmentioning
confidence: 99%
“…Oilfield produced water contains a large amount of aromatic, naphthenic and paraffinic hydrocarbons. These components are not easy to volatile and will cause immeasurable harm when entering soil and water ecosystems (Sakthipriya et al 2016, Totubaeva et al 2019. Fortunately, some studies show that Pseudomonas can degrade hydrocarbons of crude oil.…”
Section: Introductionmentioning
confidence: 99%
“…Pseudomonas and five isolates as P. fluorescens via microbiological methods and 16S rRNA sequencing (Goudarztalejerdi et al 2015). From oil polluted soil isolated P. fluorescens W3 and researchers found it quite successfully played the role of oil products decomposers (Totubaeva et al 2019).…”
Section: Introductionmentioning
confidence: 99%